Selected debate from the arena of knowledge management: new endorsements for established organizational practices - Beamish, Neal G.; Armistead, Colin G. (International journal of management reviews : IJMR, 2001)
Management theorists and practitioners have been allured recently to the contemporary field of knowledge management. This is a burgeoning subject that has enticed the involvement of specialists from established domains that are broad based in themselves: strategy, organizational behaviour, operations and information technology. In arguing the importance of knowledge in the strategic purpose of the organization, authorities essentially endorse practices that have been supported in the past: practices that appreciate the social context of knowledge. This paper reviews the debates in strategic theory that support the contemporary ‘knowledge‐based’ view of the organization, and describes how established practices relating to knowledge transfer and creation have been recently revitalized.